Standardization of lower secondary civic education and inequality of the civic and political engagement of students. Issue 3 (2nd July 2016) - Witschge, Jacqueline; van de Werfhorst, Herman G.
ABSTRACT: In this paper, the relation between the standardization of civic education and the inequality of civic engagement is examined. Using data from the International Civic and Citizenship Education Study 2009 among early adolescents and Eurydice country-level data, three-level analysis and variance function regression are applied to examine whether there is a relation between measures of civic education standardization and inequality in three dimensions of civic engagement: civic knowledge, interest in social and political issues, and participation in the community. Inequality is conceptualized as differences in students' civic engagement between schools and the association between social origin and civic engagement. The results demonstrate that accountability is associated with more inequality in civic knowledge, whereas centralization is associated with less inequality in non-cognitive civic engagement.